PENERAPAN KARAKTER MELALUI PEMBELAJARAN TERPADU DI SD - Mahfuzah, Ahya; Nurngain, Alfan (INSTRUKTUR INSTRUKTUR: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Integrated learning is a learning process that starts from a particular topic or theme that is related to other topics, concepts that are related to other concepts, which can occur spontaneously or planned, both in one or more fields of study, and with various student learning experiences. then learning becomes more meaningful. Analysis in the descriptive research method is carried out by describing the facts and then followed by analysis. The results of observations in several scientific journals show that research on the application of blended learning in elementary schools shows that incorporating character into learning can improve students' positive behavior, morals and attitudes. Based on the results of the research and discussion, it is concluded that the application of integrated learning to the application of student character at the elementary school level has a positive effect on students in practicing positive attitudes, character and morals. Not only do they know character values and integrated learning concepts, students also explore the values of cooperation, responsibility and honesty. There is the application of character and integrated learning because the learning is centered on students, the field and parental support